Double ionization of helium by 2-keV electrons in equal- and unequal-energy configurations - Ambrosio, Marcelo José (2016)
We present theoretical and experimental fully differential cross sections, in coplanar scattering geometry, for the double ionization of helium by electron impacting at 2 keV. The observed structures for both equal and unequal sharing of the excess energy are analyzed. Although the incident energy could, in principle, be regarded as high enough for the applicability of the first Born approximation in the projectile-target interaction, the experimental cross sections, measured with a COLTRIMS apparatus, show that further orders' effects can be appreciated. The theoretical cross sections are calculated with the generalized Sturmian functions method, which exactly solves the three-body problem that stems from a first-order projectile-target perturbative treatment.